Antimicrobial activity of a tissue conditioner combined with a biocide polymer - Toda, Carina [UNESP]; Marin, Danny Omar Mendoza [UNESP]; Rodriguez, Larissa Santana [UNESP]; Paleari, André Gustavo [UNESP]; Pero, Ana Carolina [UNESP]; Compagnoni, Marco Antonio [UNESP] (Jaypee Brothers Medical Publishing, 2015)
The characteristics of tissue conditioners support microorganism development that can threaten the health of the dentures user. The object of this study was to evaluate the effect on antimicrobial activity, roughness and wettability surface of a tissue conditioners material combined with the antimicrobial polymer poly (2-tert-butilaminoethyl) methacrylate (PTBAEMA). Specimens of tissue conditioner (Coe Soft(®)) were divided into three groups, according to the concentration of PTBAEMA incorporated (0, 10 and 25%). Antimicrobial activity was assessed by adherence assay of one of the microorganisms, Staphylococcus aureus, Streptococcus mutans and Candida albicans. Roughness measurements were made using a Mitutoyo SJ-400, and the mean arithmetic roughness values (Ra) obtained were used for the comparisons. The wettability properties were determined by contact angle measurements. The group containing 25% of PTBAEMA inhibited totally the S. aureus and S. mutans biofilm formation. A significant reduc tion in the S. aureus (Kruskal-Wallis, p = 0,001) and S. mutans (Kruscal-Wallis, p = 0,001) count for 10% PTBAEMA group compared with respective control group. No significant difference was found for C. albicans among PTBAEMA groups and control group (ANOVA, p > 0,05). Incorporating 10 and 25% PTBAEMA increased surface roughness and decreased contact angles (ANOVA and Tukey's post hoc tests, α = 5%). Incorporating 10% PTBAEMA into tissue conditioner increases wettability and roughness of tissue conditioner surface; and decreases the adhesion of S. mutans and S. aureus on material surface, but did not exhibit antimicrobial effect against C. albicans. The PTBAEMA incorporated into tissue conditioner could prevent biofilm formation on elderly patient.
Keywords: Antimicrobial; Biofilm; Polymer; Roughness; Tissue conditioner; Wettability